CRYPTOSPORIDIOSIS IN INDIA - ARUNAVA KALI (International Journal of Pharma and Bio Sciences, 2014)
Parasites belonging to genus Cryptosporidium constitute a large number of animal and human species of intestinal Coccidia. Among several species, C. parvum and C. muris is well recognized diarrheal agent in immune-competent as well as immunocompromised human host. Cosmopolitan distribution, stability over large variation of temperature, wide host range and zoonotic potential are the unique features which attributed to its increasing prevalence and outbreaks in most parts of the world. Owing to the large population of HIV patients in India, these infections are being increasingly reported. Furthermore, Cryptosporidium sp. has been reported as the leading cause of childhood diarrhea in India. Over the last decade, increasing awareness among clinicians and microbiologists along with introduction of simple techniques like modified acid-fast staining and stool concentration has improved the detection of these agents. However, molecular genetics of diverse human and animal species and their epidemiology and zoonotic potential need further evaluation.